2019
DOI: 10.1111/aogs.13608
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy‐corrected cervical cancer mortality rates in Denmark during 2002‐2015: A registry‐based cohort study

Abstract: Introduction We aimed to describe the cervical cancer mortality rates after correcting for hysterectomy and to evaluate trends over calendar time and by age. Material and methods Using data from nationwide registries, we calculated uncorrected and hysterectomy‐corrected cervical cancer mortality rates among women age ≥20 years in Denmark during 2002‐2015. We calculated hysterectomy‐corrected rates by subtracting post‐hysterectomy person‐years from the denominator, unless hysterectomy was performed due to cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…We would like to thank Joergensen et al, 1 for taking interest in our recently published article. 2 One of our findings, consistent with reports from other developed countries, 3 that cervical cancer mortality is highest in women aged 65 years and older, is particularly important given the increasing life expectancy, growing proportion of the population in this demographic subgroup, and debate regarding age and criteria to exit women from routine cervical cancer screening. 4 As we have highlighted in our discussion, "cervical cancer screening is associated with a lower risk of advanced stage disease and cervical cancer death".…”
Section: Sirsupporting
confidence: 87%
See 1 more Smart Citation
“…We would like to thank Joergensen et al, 1 for taking interest in our recently published article. 2 One of our findings, consistent with reports from other developed countries, 3 that cervical cancer mortality is highest in women aged 65 years and older, is particularly important given the increasing life expectancy, growing proportion of the population in this demographic subgroup, and debate regarding age and criteria to exit women from routine cervical cancer screening. 4 As we have highlighted in our discussion, "cervical cancer screening is associated with a lower risk of advanced stage disease and cervical cancer death".…”
Section: Sirsupporting
confidence: 87%
“…Trends in invitation to screening represent one additional aid to trying to understand the temporal and age-specific cervical cancer mortality trends. Our article not only outlines the important role of cervical cancer screening but also other possible reasons for the observed age-specific mortality trends: a high proportion of advanced-stage disease, high comorbidity, and a high level of frailty, which likely affects the choice of treatment, but also emphasized the need for person-level data, such as data on screening history in patients dying from cervical cancer, to best identify the causes of cervical cancer mortality in the modern era.AnneHammer 1,2…”
mentioning
confidence: 99%
“…Women who had a hysterectomy prior to 2002 did not contribute time at risk unless the procedure was performed due to uterine cancer. Acknowledging that some women may have undergone hysterectomy prior to the establishment of the DNPR in 1977, we made additional correction of person‐time at risk considering the probability of hysterectomy prior to 1977 for women aged 35 years or older, as described previously 24,25 . In the present study, we primarily present hysterectomy‐corrected rates, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Hammer et al found a sharp increase in cervical cancer mortality in women older than 65 years and called for future studies to focus on understanding the underlying reasons for the high mortality rate in older Danish women. In their study they seem to have overlooked that a non‐negligible proportion of these older women had never been screened.…”
mentioning
confidence: 99%
“…In the report published by Hammer et al, cervical cancer mortality during 2002‐2015 among women aged 60‐64 years (the lowest square, Figure ) was calculated in birth cohorts where close to 100% were invited to screening. In contrast, mortality among women aged 65+ was calculated in birth cohorts where an increasing proportion of women have not been invited to screening (top 4 squares, Figure ).…”
mentioning
confidence: 99%